2002
DOI: 10.1212/wnl.59.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Developmental language disorder associated with polymicrogyria

Abstract: Developmental language disorder can be associated with polymicrogyria and the clinical manifestation varies according to the extension of cortical abnormality. A subtle form of posterior parietal polymicrogyria presenting as developmental language disorder is a mild form of perisylvian syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
1
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 19 publications
3
62
1
8
Order By: Relevance
“…Bilateral perisylvian polymicrogyria (BPP) is usually symmetrical and genetically heterogeneous. 12 Mutations of SRPX2 have been related to BPP, but the role of this gene needs to be confirmed. 2 Asymmetric BPP, with a striking predisposition for the right hemisphere, has been associated with 22q11.2 deletions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral perisylvian polymicrogyria (BPP) is usually symmetrical and genetically heterogeneous. 12 Mutations of SRPX2 have been related to BPP, but the role of this gene needs to be confirmed. 2 Asymmetric BPP, with a striking predisposition for the right hemisphere, has been associated with 22q11.2 deletions.…”
Section: Discussionmentioning
confidence: 99%
“…2 Asymmetric BPP, with a striking predisposition for the right hemisphere, has been associated with 22q11.2 deletions. 12 Mutations of GPR56 have been reported in patients with bilateral frontoparietal polymicrogyria, 4 a recessive disorder with MRI characteristics resembling those of the cobblestone malformations spectrum. 2 TUBB2B mutations have previously been associated with anteriorly predominant asymmetrical polymicrogyria, 5 more severe in the fronto-parietal areas, and involving the perisylvian region with left-sided predominance.…”
Section: Discussionmentioning
confidence: 99%
“…DEL se caracteriza por aquisição inadequada de linguagem em crianças sem qualquer outra alteração do desenvolvimento cognitivo. São crianças que apresentam audição normal à audiometria, ausência de t r a n s t o rnos cerebrais crônicos pela avaliação neurológica clínica, ausência de alteração estrutural na m o rfologia bucal e discrepância entre habilidades intelectuais verbais e não verbais (sendo estas geralmente norm a i s ) 1 . Alguns podem apresentar dislexia na evolução.…”
Section: Discussionunclassified
“…S í n d rome peri-sylviana (SP) ou opercular re f e rese a diversas manifestações clínicas que podem a c o mpanhar lesões que comprometem a região peri-sylviana ou operc u l a r 1 . A primeira descrição de quadro clínico correlacionado com lesão peri-sylviana foi de Foix, Chavany e Marie, em 1926, que re l a t a r a m q u a d ro de diplegia facioglossofaringo-mastigatória conseqüente a acidente vascular cerebral bi-lateral ao redor da fissura de Sylvius.…”
unclassified
“…Guerreiro et al 29 observed that language disorder may be associated with PMG. The authors described a mild form of posterior parietal PMG where the abnormal cortex extends around a continuum of the Sylvian fissure in patients with language disorder 30 .…”
Section: Malformations Due To Abnormal Cortical Organization Polymicrmentioning
confidence: 99%